Zinc(II)‐N2O2 ligation complex‐based DNA/protein binder and cleaver having enhanced cytotoxic and phosphatase activity. (29th May 2018) - Neelakantan, M.A.; Balakrishnan, C.; Balamurugan, K.; Mariappan, S.S.
Abstract : The alkyne arms containing zinc(II) N2 O2 ligation complexes (1 ) and (2 ) were prepared from 2, 2′‐cyclohexane‐1, 2‐diylbis[nitrilo(E)methylylidene]bis[5‐(prop‐2‐yn‐1‐yloxy)phenol] (L 1 ) and 2, 2′‐1, 2‐phenylenebis[nitrilo(E)methylylidene]bis[5‐(prop‐2‐yn‐1‐yloxy)phenol] (L 2 ) and characterized by analytical and various spectral techniques. The molecular geometry of1 and2 was optimized by Density Functional Theory (DFT) at B3LYP/6‐311G(d, p) level and compared with literature. The complexes are stable in solution, and their solution structure was assessed using NMR and ESI‐MS spectroscopy. Topological analysis of the electron density and nature of the bonding in the complexes has been determined by using Bader's AIM method. The interaction and binding modes of calf thymus DNA (CT‐DNA) with complexes (1 and2 ) were investigated by using absorption and emission spectral and viscometric studies. The nuclease activity investigated through gel electrophoresis reveals that1 and2 exhibits a significant DNA cleavage activity via a hydrolytic pathway and is further confirmed by an experiment performed in the presence of T4 ligase. The protein binding ability of1 and2 with bovine serum albumin (BSA) protein evaluated show good protein binding propensity. In‐vitro cytotoxicity of the complexes has shown significant activity against human brain tumor (U87 MG) and breast carcinoma (BT20) cancer cell lines. The comet assay has been used to determine the extent of DNA fragmentation in cancer cells. The phosphatase activity investigated through kinetic measurements establishes that the zinc complexes possess significant hydrolytic efficiency and follow the order2 > 1 . The DFT calculations have also been carried out to support the proposed mechanistic pathway of catalytic activity. Abstract : Alkyne arms containing zinc(II) N2 O2 ligation complexes were synthesized and characterized. Topological analysis of the electron density and the nature of bonding in the complexes were determined. The DNA/BSA binding interactions, cytotoxicity and phosphatase activity were studied.